EXPLORING VOCABULARY ENRICHMENT AN EXPERIMENTAL INVESTIGATION USING THE TIKTOK SOCIAL MEDIA PLATFORM - Ramadani, Mahruji Robiatu (Universitas Cokroaminoto Palopo, 2024)
This experimental study investigates the possibility of using Antonio Parlati's account on the social media site Tik-Tok as a useful tool to improve students' vocabulary in English. Pre-tests, mid-tests, and post-tests are used in a quasi-experimental design to examine how Tik-Tok affects vocabulary development. Through his Tik-Tok films, Italian content creator Antonio Parlati, who specializes in English language acquisition, offers insightful lexical content. The study involves 20 students of X grade class, ages 15 to 17, and the Tik-Tok App Knowledge Test is used for evaluation. The findings show that individuals' vocabulary learning has improved to differing degrees; terms like